2018
DOI: 10.1002/adbi.201700184
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Genome Editing Using Gold‐Nanoparticle‐Mediated Laserporation

Abstract: Engineered nucleases hold large potential for future gene therapy applications. An obstacle hampering their applications are delivery methods bearing efficiency, throughput, and viability of target cells. How this limitation can be overcome via gold‐nanoparticle‐mediated (GNOME) laserporation is demonstrated. It employs a picosecond laser setup and 200 nm gold nanoparticles, and its full capacity with CRISPR/Cas9 delivery is demonstrated. 70 kDa dextrans are utilized to probe delivery in adherent SC1 cells. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…To test if Cas9-Hoxb8 cell-derived DCs rely on the same mechanisms and thus can be exploited as a tool to study DC migration, we used lentiviral-based CRISPR/Cas9 technology to knockout Ccr7 . Cas9-Hoxb8 cells were transduced with a lentivirus expressing dTomato (dTom) and sgRNA targeting Ccr7 ( 30 ). Successfully transduced cells were purified by fluorescence-activated cell sorting based on dTom expression and subsequently differentiated into DCs in the presence of GM-CSF followed by the treatment with LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test if Cas9-Hoxb8 cell-derived DCs rely on the same mechanisms and thus can be exploited as a tool to study DC migration, we used lentiviral-based CRISPR/Cas9 technology to knockout Ccr7 . Cas9-Hoxb8 cells were transduced with a lentivirus expressing dTomato (dTom) and sgRNA targeting Ccr7 ( 30 ). Successfully transduced cells were purified by fluorescence-activated cell sorting based on dTom expression and subsequently differentiated into DCs in the presence of GM-CSF followed by the treatment with LPS.…”
Section: Resultsmentioning
confidence: 99%
“…Protospacer sequences were designed with the online tools CRISPR Design ( http://crispr.mit.edu/ ) (Zhang Lab, MIT, 2015) or CCTop ( https://crispr.cos.uni-heidelberg.de/ ) ( 29 ). Generation of pLKO5.hU6.sgRNA.Ccr7.SFFV.dTomato.PRE is described elsewhere ( 30 ). Lentiviral vectors expressing sgRNAs targeting Cxcr4 and Trpml were cloned as follows: designed sequences were ordered as oligonucleotides carrying BsmBI overhangs at their 5′-ends.…”
Section: Methodsmentioning
confidence: 99%
“…AuNP-sensitized VNB photoporation is an emerging approach for the safe and efficient intracellular delivery of macromolecules in a broad range of cell types [31,34,35,42,43]. Previously, our group and others already demonstrated the use of the technique for the delivery of macromolecules in murine CD8+ T cells [35,44], but so far, the applicability for primary human CD4+ T cells remained elusive. In this study, we evaluated AuNP-sensitized VNB photoporation for the intracellular delivery of model macromolecules of increasing molecular weight in hard-to-transfect Jurkat and primary human CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18,19 ] In the past decade, photoporation with AuNPs has been successfully used to deliver a wide variety of molecules in many different cell types, including in primary murine and human T cells. [ 14,18,23,24 ] However, clinical translation of this technology for the production of engineered therapeutic cells is still a bottleneck due to the fact that AuNPs are not biodegradable. In addition, it has been repeatedly shown that AuNPs fragment into small pieces of several nanometers (<10 nm) after being exposed to pulsed laser irradiation.…”
Section: Introductionmentioning
confidence: 99%